IMPLEMENTASI HAK PENDIDIKAN ANAK PERSPEKTIF AL-QUR’AN DI SDS JAKARTA ISLAMIC SCHOOL - Farizal MS; Hendra Surahman (Jurnal Statement : Media Informasi Sosial dan Pendidikan, 2022)
This research is a field research with a descriptive qualitative approach. Implementation of the Right to Education of Children from the Al-Qur'an Perspective at SDS Jakarta Islamic School, Joglo, Kembangan, West Jakarta. Problems that are within the scope of a family and school in the form of children's delinquency, disobedience to their parents and teachers, lack of attention from their parents and so on identify that there are problems in the family and in the learning place, then to what extent the position of educators and families can provide rights education for students and or their children in accordance with the teachings of Islamic law through the perspective of the Qur'an. There are seven children's rights that they must always receive and receive from their parents and educators, including: the Right to Faith and Tawhid Education, the Right to Worship Education, the Right to Moral Education, the Right to Physical Education, Furthermore, the Right to Intellectual Education, the Right to Mental Education and ends with the Right to Education. Social. So, by implementing the right to Al-Qur'anic Children's Education at SDS Jakarta Islamic School, West Jakarta, it has made a good and positive contribution to the educational development of students